THE TEACHERS' CLINIC. - Carson, A. B.; Gordon, Dennis; Anderson, Rae D.; Sadler, Alton G.; Homburger, Richard H. (The Accounting Review, 1958)
Abstract More than 600,000 young men and women are expected to pursue programs in collegiate business education by 1970. This will double the present enrollment, according to the American Association of Collegiate Schools of Business. Unless drastic steps are taken there will be a shortage of 2,800 teachers in business schools and departments alone. Accounting departments will be among the first to feel the impact of this "impending tidal wave" of students. A round table discussion to consider what accounting departments could do to meet the many problems associated with increasing enrollments was conducted at the 1957 American Accounting Association Convention. In preparation for the session the chairmen undertook an analysis of present teaching practices in elementary accounting throughout the country in the hope that the information collected would be useful in evaluating the different solutions that might be proposed. At the same time, accounting teachers should be preparing themselves for the parts which they are to play in planning their participation in the education of young people in and out of college about the developments in the field of electronic data processing. The purpose of this article is to give accounting teachers a point of contact with electronic data processing, omitting specialized terms and techniques, with sufficient information, so that interest may be created and action may be taken in changing curricula in accounting.